PERSEPSI DOSEN, MAHASISWA (PPAk), MAHASISWA AKUNTANSI DAN PENGGUNA JASA TERHADAP DUE AUDIT CARE AKUNTAN PUBLIK - Atiek Sri Purwati; Krishnoe Rachmi Fitrijati (Fakultas Ekonomi Universitas Pekalongan, 2015)
The purpose of the research was to examine the perception of Accounting students, Lecturer, ProffesionalAccounting students and clients in Purwokerto related to public accountant’s due audit care. Furthermore, thisstudy was to recognize significant difference of perception among respondents about five determinants of dueaudit care which are consist of planning and supervision, internal control system, audit evidence, audit reportand internal and external condition.The research applied the survey method. The sampling method was purposive sampling from population. Thesample of research is 250 responden. Collected data was analyzed by one sample t -test and independentsample t-test (pooled varians t-test). The research implies that (1) according to respondents, auditors have notapplied due audit care as required by auditing proffesional ethics (2) There are no significant difference ofperception among respondents about five determinants of due audit care.Keywords: due audit care, perception